Box-scheme as alternative food network - the economic integration between consumers and producers - Ronaldo Tavares de Souza (Agricultural and Food Economics, 2020)
As a growing option for small farmers, alternative food networks (AFN) have attracted the attention of researchers around the world. Nevertheless, not much focus is given to box-schemes as a format itself. The nomenclature is often associated with community-supported agriculture (CSA) and solidarity purchase groups (SPG), but many companies have reduced geographic and informational distances without demanding such a narrow relationship between collaborators. The aim of this article is to analyze the relationship between companies and their customers. A theoretical framework was built based on thoughts about economic integration and the relationship in the retail environment to examine the possibility of reciprocity and redistribution. The fieldwork was conducted in S\~ao Paulo, Brazil. Technology is found to be fundamental to the rise of such companies, but the Internet is not the only key, the telephone is also important for a warmer and closer relationship. The interviews revealed different signals of reciprocity supporting a trusting relationship while the occasional buyers demonstrate more opportunistic behaviors. Of the cases studied, one successful company demonstrated signs of reciprocity between companies and customers, as well as customer integration based on redistribution characteristics. This confirmed the possibility of the boxscheme contributing to rural sustainability, related to customers who have built a broader perspective, going beyond price and quality. The article concludes defending that this format of commerce should be further studied to confirm its capacity to support rural development and continue to deepen the understanding of the conditions that can make it successful.
Keywords: 330; Alternative food network; Box-scheme; Rural development; Food retail; Responsible consumption